Analysis on Policy Gender Based Differentiated Class Toward ELT Learning - Siti Aminah (Journal of Education, Linguistics, Literature and Language Teaching, 2023)
This study aimed to find out the attitudes and students' perspectives on the policy-based differentiated class toward ELT learning. This study used a qualitative approach with a case study research type. It involved 50 students in grade VIII of Muhammadiyah Langsa Middle School, consisting of two classes: class VIIIC for girls and class VIII E for boys. In collecting data for this study, the researchers used class observation sheets, interviews, questionnaires, and documentation. Data from observations and interviews indicated that the attitudes of teachers and students in the classroom were very good. Teachers did not discriminate against students, gave them the freedom to express their opinions, and students were free to express themselves and confident in learning. Students were also able to participate well in the classroom. Meanwhile, the results of the questionnaire showed that students' perspectives on this class policy had a positive value. Students felt that ELT learning in gender-differentiated classes was more enjoyable than in mixed classes. They also felt more comfortable and free from interference from the opposite sex when studying ELT, and according to them, gender differentiated class policies made them more focused when studying ELT in class.